2018
DOI: 10.1002/prp2.392
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the putative role of heme as a trigger of inflammation

Abstract: Activation of the innate immune system by free heme has been proposed as one of the principal consequences of cell‐free hemoglobin (Hb) exposure. Nonetheless, in the absence of infection, heme exposures within a hematoma, during hemolysis, or upon systemic administration of Hb (eg, as a Hb‐based oxygen carrier) are typically not accompanied by uncontrolled inflammation, challenging the assumption that heme is a major proinflammatory mediator in vivo. Because of its hydrophobic nature, heme liberated from oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 34 publications
(75 reference statements)
2
48
0
1
Order By: Relevance
“…It has to be noted that heme, as a free circulating molecule, is currently debated because of its substantial hydrophobicity, the high concentration of heme-binding plasma proteins and the lack of validated, reliable tests to measure the free heme levels in plasma in clinical settings (5,108). It is still unknown what is the exact free heme concentration in the context of SCD and during DHTR.…”
Section: Complement Activation By Cell-free Hemementioning
confidence: 99%
“…It has to be noted that heme, as a free circulating molecule, is currently debated because of its substantial hydrophobicity, the high concentration of heme-binding plasma proteins and the lack of validated, reliable tests to measure the free heme levels in plasma in clinical settings (5,108). It is still unknown what is the exact free heme concentration in the context of SCD and during DHTR.…”
Section: Complement Activation By Cell-free Hemementioning
confidence: 99%
“…Thus, we demonstrate herein that hemolytic processes are associated with the generation of S100A8 and that some of the inflammatory effects of heme may be amplified by the autocrine production of the alarmin, S100A8. As highly hydrophobic heme is rapidly bound to and neutralized by molecules, such as hemopexin or albumin, or lipids, it has been suggested that heme may modulate inflammation via more complex models of sequential priming and activation processes . Our findings suggest a mechanism by which hemolytic inflammation could be propagated via leukocyte priming by endogenous proteins, even in sterile inflammatory environments, such as those that occur in the hemolytic diseases, following mechanical trauma and during transfusion reactions.…”
Section: Resultsmentioning
confidence: 68%
“…Once in the circulation, cell‐free Hb is swiftly oxidized, and releases hemin (or heme), a hydrophobic molecule, now recognized as a red cell danger‐associated molecular pattern (DAMP) . Cell‐free Hb and heme are usually neutralized by endogenous scavenger proteins, such as haptoglobin and heme‐binding hemopexin; however, when intravascular hemolysis is excessive, scavenging mechanisms can become depleted, enabling heme‐induced damage and lipid oxidation . Reports show that heme can activate neutrophil extracellular trap (NET) production, stimulate TLR4‐mediated endothelial activation, and induce inflammasome formation in primed Mϕ s and endothelial cells …”
Section: Introductionmentioning
confidence: 99%
“…15,16 In mice with SCD, heme infusion has been shown to induce TLR4mediated endothelial activation and microvascular stasis, and trigger ACS. 17 The proinflammatory effects of heme released during hemolysis, in in vivo situations, have though been questioned, since highly hydrophobic heme is rapidly bound to and neutralized by macromolecules, such as hemopexin or albumin, or lipids 18 ; however, hemopexin levels are significantly depleted in SCD 19,20 and it is possible that heme may modulate inflammation in more complex models of sequential priming and activation processes. 18 Vaso-occlusive processes are a defining characteristic of SCD, where they occur principally in the microcirculation, reducing tissue oxygenation and inducing tissue damage.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%
“…17 The proinflammatory effects of heme released during hemolysis, in in vivo situations, have though been questioned, since highly hydrophobic heme is rapidly bound to and neutralized by macromolecules, such as hemopexin or albumin, or lipids 18 ; however, hemopexin levels are significantly depleted in SCD 19,20 and it is possible that heme may modulate inflammation in more complex models of sequential priming and activation processes. 18 Vaso-occlusive processes are a defining characteristic of SCD, where they occur principally in the microcirculation, reducing tissue oxygenation and inducing tissue damage. Inflammatory cell activation leads to the production and secretion of molecules such as cytokines and chemokines, growth factors, eicosanoids, and peptides that propagate the inflammatory state and further activate other cells in the vasculature.…”
Section: Pathophysiology Of Scdmentioning
confidence: 99%